Diversity and resistance profile of bacteria associated with washroom surfaces in Bangladesh Agricultural University residence halls - Md. Shafiqul Islam; Sabrina Sultana Rimi; Md. Nahid Ashraf; Sanzila Hossain Sigma; Sharika Jahan; Mahbubul Pratik Siddique; Md.Tanvir Rahman (Journal of Advanced Biotechnology and Experimental Therapeutics, 2025)
Public washrooms in shared spaces, such as university residence halls, serve as potential reservoirs for pathogenic and multidrug-resistant bacteria, posing significant public health risks. This study aimed to assess bacterial diversity and evaluate antibiotic resistance profiles on commonly touched surfaces in washrooms and toilets of BAU residence halls. In total, 80 swab samples were obtained from the toilet and bathroom surfaces. Bacterial load was determined from each sample by total viable count (TVC), total coliform count (TCC), and total staphylococcal count (TSC). The bacterial isolates were identified using staining, biochemical testing, and subsequent molecular identification. Afterward, thirteen commonly available antibiotics were used to investigate the antibiotic sensitivity of the isolated organisms by disk diffusion methods. In the washroom samples, the greatest mean values were for TVC (log 5.91), TCC (log 5.75), and TSC (log 5.96). On the other hand, the toilet samples had the lowest mean values for TVC (log 5.39), TCC (log 5.13), and TSC (log 5.47). Notably, the floor surface samples had the highest levels of TVC, TCC, and TSC. The overall prevalence of E. coli, Staphylococcus aureus, and Klebsiella spp. was found to be 71%, 93.75%, and 87.5%. All isolated bacteria were found to be sensitive to chloramphenicol and gentamycin and resistant to ampicillin and amoxicillin. The study also found Methicillin-Resistant Staphylococcus aureus (MRSA), which poses a risk to public health. Therefore, the findings of this study can guide better hygiene practices, antibiotic usage, infrastructural improvements, and MRSA control in shared restrooms. [ J Adv Biotechnol Exp Ther 2025; 8(2.000): 232-241]